Oposisi Biner dalam “Lettres de Mon Moulin” Karya Alphonse Daudet - Rifqi Ayu Everina (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2021)
Binary opposition is the most important aspect that can reveal how humans think, how humans produce meaning and understand reality (Culler, 1976). Therefore, the discovery of binary oppositions is useful in providing clues to the workings of human reason. In the context of narrative analysis, binary opposition can reveal how the logic behind a narrative is made. Based on this, this study highlights how the formation of binary opposition contained in the novel